2002
DOI: 10.1097/00000542-200212000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acustimulation and Ondansetron for the Treatment of Established Postoperative Nausea and Vomiting

Abstract: Acustimulation with the ReliefBand can be used as an alternative to ondansetron for the treatment of established PONV. However, the use of ondansetron (4 mg intravenously) in combination with the ReliefBand device improved the complete response rate to the acustimulation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 0 publications
0
23
0
3
Order By: Relevance
“…Coloma et al [11] compared TENS with ondansetron after antiemetic prophylaxis in patients who had undergone laparoscopic surgery and suggested TENS as an alternative to ondansetron in preventing PONV. White et al [12] compared acustimulation with ondansetron (4 mg IV) when used as prophylaxis against PONV.…”
Section: Discussionmentioning
confidence: 99%
“…Coloma et al [11] compared TENS with ondansetron after antiemetic prophylaxis in patients who had undergone laparoscopic surgery and suggested TENS as an alternative to ondansetron in preventing PONV. White et al [12] compared acustimulation with ondansetron (4 mg IV) when used as prophylaxis against PONV.…”
Section: Discussionmentioning
confidence: 99%
“…When used for prophylaxis, the combination of ondansetron and acupoint electrical stimulation was associated with lower incidence of PONV, less need for rescue antiemetics as well as improved quality of recovery and patient satisfaction, compared to ondansetron alone. 113,114 Hypnosis has also been found effective when compared with placebo (IIIB). 115 Although some earlier reports suggested that ginger root might have a beneficial effect for PONV prophylaxis, this has not been confirmed in a recent meta-analysis (IIA).…”
Section: Non-pharmacological Techniquesmentioning
confidence: 99%
“…In Chinese medicine, P6 point is called as the peak of body energy 8 and therefore, when Acupressure is competently applied, the body's energy balance will be restored. In other studies, the effect of Acupressure at P6 was confirmed in various medical interventions 9,10 . However, these results were in contrast with those of other studies [11][12][13] .…”
Section: Resultsmentioning
confidence: 64%